Spectrophotometric analysis of caffeine in local product of Arabica: observed at different roasted temperatures. Issue 1 (August 2021) - Misto,; Alawiyah, K; Rohman, L; Supriyadi,; Mutmainnah,; Purwandari, E
Abstract: Indonesia's geographical location supports the existence of various coffee commodities. As a plantation commodity, coffee has a high economic value. Coffee has a lot of substance that is beneficial to the body, one of is caffeine that serve to increase the stamina. Caffeine is naturally present in many types of plants as secondary metabolism. This research was done to know the content of caffeine in a local Arabica pure coffee with their variation of roasted temperatures. Coffee roasting is a stage of processing coffee beans into ready to grind, which can produce variations in the taste and content of coffee. The roasting process uses a roasting machine that automatically adjusts the roast temperature. Variations of roasted coffee are ground and used as a solution to determine the caffeine content. The determination of the coffee content is carried out using the spectrophotometric method, which measures the absorbance of caffeine in solution when it is passed by electromagnetic waves in the UV-Vis spectrum. The test results showed that the highest caffeine content was on samples of pure Arabica coffee with a roasted temperature of 195°C to 215°C with five levels of coffee roast. Caffeine content in sequential 3.217% and 2.597%.